Identifying Combinations of Individual Governance Indicators Essential for Attracting International Capital Flows to Asian Economies - Shamsub, Hannarong; Haque, Mahfuzul (Journal of Social Economics Research, 2021)
This study identifies essential combinations of individual governance indicators which influence inward capital flows for a group of seven highly interdependent Asian economies from 1997 to 2017. The panel data was estimated using a Seemingly Unrelated Regression (SUR) model. The findings show that selected governance indicators influence capital inflows together with traditional push and pull economic factors, such as global liquidity, global GDP growth, stock market return, and GDP growth. The study discovered two essential combinations of governance indicators which attract inward capital flows, one influencing portfolio inflow and the other influencing foreign direct investment (FDI). The two combinations of individual governance indicators supplement the role of traditional economic drivers of portfolio investment and FDI. The findings offer some policy implications; policies intending to attract capital flows into the local economies by offering only push and pull economic factors, such as improving the macroeconomic environment, may not be sufficient in the absence of improvement in governance quality. However, not all individual governance indicators are equally important as drivers of capital flows. The two essential combinations of governance factors found in this study should be given top priority for improvement if policymakers intend to attract more portfolio inflows and FDI.